1991
DOI: 10.1128/jb.173.18.5648-5652.1991
|View full text |Cite
|
Sign up to set email alerts
|

Arc and Sfr functions of the Escherichia coli K-12 arcA gene product are genetically and physiologically separable

Abstract: The Escherichia coli arcA gene product regulates chromosomal gene expression in response to deprivation of oxygen (Arc function; Arc stands for aerobic respiration control) and is required for expression of the F plasmid DNA transfer (tra) genes (Sfr function; Sfr stands for sex factor regulation). Using appropriate lacZ fusions, we have examined the relationship between these two genetic regulatory functions. Arc function in vivo was measured by anaerobic repression of a chromosomal sdh-lacZ operon fusion (sd… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
13
0

Year Published

1992
1992
2016
2016

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(14 citation statements)
references
References 27 publications
1
13
0
Order By: Relevance
“…Notable modifications include deletions in adhE, ldhA, pflB, mdh, and mutated versions of gltA, lpdA, and arcA. The arcA mutation, resulting in an 8 amino acid insertion in the ArcA protein (Iuchi and Lin, 1988;Silverman et al, 1991) renders the regulator largely inactive, and thus activates the oxidative TCA flux under low O2 conditions (Yim et al, 2011). The gltA and lpdA mutations are the same as described in (Yim et al, 2011).…”
Section: Bacterial Strainmentioning
confidence: 99%
“…Notable modifications include deletions in adhE, ldhA, pflB, mdh, and mutated versions of gltA, lpdA, and arcA. The arcA mutation, resulting in an 8 amino acid insertion in the ArcA protein (Iuchi and Lin, 1988;Silverman et al, 1991) renders the regulator largely inactive, and thus activates the oxidative TCA flux under low O2 conditions (Yim et al, 2011). The gltA and lpdA mutations are the same as described in (Yim et al, 2011).…”
Section: Bacterial Strainmentioning
confidence: 99%
“…Several host-encoded proteins also influence expression from P Y . The transcriptional activator SfrA (47,53) and integration host factor (49) both influence tra operon expression and F plasmid transfer. Silverman et al (48) observed that cpxA deletion mutants exhibited quasi-wild-type levels of Flac transfer.…”
mentioning
confidence: 99%
“…ArcA (or SfrA, for sex factor regulation) is also required for expression of the tra (DNA transfer) genes of the F plasmid. In this function, CpxA, instead of ArcB, might act in conjunction with ArcA (18,30,32,33,38).…”
mentioning
confidence: 99%
“…ArcA (or SfrA, for sex factor regulation) is also required for expression of the tra (DNA transfer) genes of the F plasmid. In this function, CpxA, instead of ArcB, might act in conjunction with ArcA (18,30,32,33,38 (21), and in the case of the sensor FrzE of Myxococcus xanthus, an Asp residue(s) has been shown to undergo autophosphorylation (26). In contrast, ArcA is a typical regulator protein, with only the receiver domain containing conserved Asp residues at positions 11 and 54 as potential sites for transphosphorylation by phosphorylated ArcB (ArcB-P) (4,20).…”
mentioning
confidence: 99%